High-performance hard carbon anode material for lithium battery and preparation method thereof

CN122916094APending Publication Date: 2026-10-16DONGGUAN XINKODA ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610865992.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有硬炭负极材料在使用过程中,由于其丰富的纳米孔道和缺陷位点在首次充放电时消耗大量锂离子形成过厚的固态电解质膜,造成不可逆容量损失,同时,为提高容量而采用的造孔策略往往削弱碳骨架结构,导致循环过程中孔道塌陷、容量快速衰减,导致整体性能较差

Benefits of technology

1.本发明中,本发明通过配位-交联杂化网络,使第一金属、第二金属、硅及锂组分在分子尺度上均匀分散,碳化过程中,第一金属转化为耐高温氧化物纳米晶,有效抑制碳层有序化堆叠,扩大碳层间距,为锂离子提供更充分的嵌入脱出空间,第二金属原位生成可酸溶性氧化物纳米颗粒,作为自模板经酸洗脱除后形成由超微孔与介孔组成的多级孔道结构,显著增加储锂活性位点,液相浸渍的甲酸锂碳化后形成锂氧碳键合结构,预先消耗不可逆嵌锂位点,协同作用下,硬炭负极材料的首次库仑效率与可逆比容量均得到提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916094A_ABST
    Figure CN122916094A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium batteries, in particular to a high-performance hard carbon negative material for lithium batteries and a preparation method thereof, which comprises the following steps: multi-element composite liquid preparation: adding m-hydroxybenzoic acid, a first compound, a second compound, tetraethyl orthosilicate and an organic acid catalyst into a treatment solvent, stirring and reacting at 40-80 DEG C for 0.5-2 hours to obtain a multi-element composite liquid. In the application, the first metal is converted into high-temperature-resistant oxide nanocrystals, the ordered stacking of carbon layers is effectively inhibited, the carbon layer spacing is expanded, more sufficient embedding and disembedding spaces for lithium ions are provided, the second metal generates acid-soluble oxide nanoparticles in situ, the multi-stage pore structure composed of ultramicropores and mesopores is formed after the nanoparticles are removed through acid washing as a self-template, the lithium storage active sites are significantly increased, the lithium carbonate bonding structure is formed after the lithium formate is carbonized through liquid immersion, the irreversible lithium embedding sites are pre-consumed, and the first coulomb efficiency and the reversible specific capacity of the hard carbon negative material are both improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, specifically to a high-performance hard carbon anode material for lithium batteries and its preparation method. Background Technology

[0002] In recent years, the rapid development of portable electronic products such as mobile phones, tablets, and laptops, as well as the increasing popularity of new energy electric vehicles, has led to a growing demand for energy storage systems. Compared with traditional lead-acid batteries, lithium-ion batteries have advantages such as high energy density, low toxicity, and long cycle life, and are therefore widely used in the field of consumer electronics. Carbon materials, as anode materials for lithium-ion batteries, have not only been extensively studied, but are also one of the most widely used anode materials in the commercial market, mainly because of their advantages such as good safety performance, excellent cycle performance, and high energy density. The most common carbon materials include the following: graphite, carbon fiber, mesophase carbon microspheres, pyrolytic carbon, hard carbon, porous carbon, carbon nanotubes, and graphene.

[0003] Existing hard carbon anode materials suffer from irreversible capacity loss during use because their abundant nanopores and defect sites consume a large number of lithium ions during the first charge and discharge cycle, forming an excessively thick solid electrolyte film. At the same time, the pore-forming strategies adopted to improve capacity often weaken the carbon skeleton structure, leading to pore collapse and rapid capacity decay during cycling, resulting in poor overall performance.

[0004] Based on this, the present invention provides a high-performance hard carbon anode material for lithium batteries and its preparation method. Summary of the Invention

[0005] The purpose of this invention is to provide a high-performance hard carbon anode material for lithium batteries and its preparation method. The hard carbon anode material prepared by this invention not only has a good specific capacity, but also has excellent initial coulombic efficiency and cycle life.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high-performance hard carbon anode material for lithium batteries, comprising the following steps: S1: Preparation of multi-component composite liquid: In the treatment solvent, phloroglucinol, compound one, compound two, tetraethyl orthosilicate and organic acid catalyst are added, and the mixture is stirred at 40-80℃ for 0.5-2h to obtain multi-component composite liquid; S2: Crosslinking reaction: Terephthalaldehyde and organic acid catalyst are added to the multi-component composite liquid and reacted at 50-70℃ for 1-3 hours. Then, dimethoxymethane is added and reacted in a closed system at 100-120℃ for 6-8 hours to obtain a double crosslinked polymer. S3: Liquid phase lithium doping: Prepare lithium formate solution, immerse the double cross-linked polymer in lithium formate solution, ultrasonically disperse for 10-30 min, and then vacuum evaporate the solvent at 40-60℃ to obtain intermediate; S4: Segmented carbonization: The intermediate is placed in an inert atmosphere and subjected to segmented carbonization to obtain the crude carbonized product. S5: Acid washing and drying: The crude carbonized product is acid washed, water washed and dried to finally obtain high-performance hard carbon anode material for lithium batteries.

[0007] Preferably, the treatment solvent is prepared by mixing at least one of ethylene glycol dimethyl ether, tetrahydrofuran, dioxane, and N,N-dimethylformamide with deionized water at a volume ratio of 9 to 49:1, and the total water content of the solvent system is 2 to 10 wt%.

[0008] Preferably, the mass ratio of the treatment solvent to phloroglucinol is 5 to 20:1.

[0009] Preferably, the weight ratio of the phloroglucinol, the first compound, the second compound, tetraethyl orthosilicate, lithium formate, terephthalaldehyde, dimethoxymethane, and the organic acid catalyst is as follows: phloroglucinol 80-120 parts, the first compound 5-20 parts, the second compound 2-8 parts, tetraethyl orthosilicate 6-15 parts, lithium formate 1-5 parts, terephthalaldehyde 30-50 parts, dimethoxymethane 15-30 parts, and the organic acid catalyst 0.5-4 parts.

[0010] Preferably, the first compound is zirconium n-propoxide or tetrabutyl titanate, the second compound is zinc isopropoxide or magnesium isopropoxide, and the organic acid catalyst is p-toluenesulfonic acid.

[0011] Preferably, based on the amount of resorcinol, the molar ratio of the first compound to resorcinol is 0.03 to 0.10:1, the molar ratio of the second compound to resorcinol is 0.01 to 0.05:1, the molar ratio of lithium formate to resorcinol is 0.02 to 0.10:1, and the molar ratio of tetraethyl orthosilicate to resorcinol is 0.05 to 0.20:1.

[0012] Preferably, in S1, the amount of organic acid catalyst added is 20% to 50% of the total amount of catalyst, and the remaining catalyst is added together with terephthalaldehyde in S2.

[0013] Preferably, in step S3, the lithium formate solution is prepared by dissolving lithium formate in anhydrous ethanol and stirring at 100-300 r / min for 10-30 min at 20-40°C to prepare a lithium formate solution with a concentration of 0.1-0.5 mol / L. The liquid-solid mass ratio of the lithium formate solution to the double crosslinked polymer is 3-8:1.

[0014] Preferably, the segmented carbonization in S4 adopts a continuous heating program: heating from room temperature to 180-250℃ at 0.5-1℃ / min and holding for 1-3 hours; then heating to 300-400℃ at 1-2℃ / min for pre-carbonization for 0.5-1.5 hours; then heating to 600-700℃ at 2-3℃ / min and holding for 0.5-1 hours; finally heating to 850-1050℃ at 2-5℃ / min and holding for 1-3 hours, and then naturally cooling to room temperature after carbonization. The inert atmosphere is high-purity nitrogen.

[0015] Preferably, in step S5, the pickling is performed using hydrochloric acid with a concentration of 0.3–1 mol / L at 60–90°C for 2–6 hours. After pickling, the solution is washed with pure water at 60–80°C until it is neutral and has a conductivity ≤50 μS / cm. The drying conditions are vacuum drying at 80–120°C for 6–12 hours.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, a coordination-crosslinking hybrid network is used to uniformly disperse the first metal, the second metal, silicon, and lithium components at the molecular scale. During carbonization, the first metal is transformed into high-temperature resistant oxide nanocrystals, which effectively inhibits the ordered stacking of carbon layers, expands the carbon layer spacing, and provides more space for lithium ions to insert and extract. The second metal is generated in situ into acid-soluble oxide nanoparticles, which serve as self-templates. After being removed by acid washing, they form a multi-level pore structure composed of micropores and mesopores, which significantly increases the active sites for lithium storage. After carbonization, the liquid-impregnated lithium formate forms a lithium-oxygen-carbon bonded structure, which pre-consumes irreversible lithium insertion sites. Under the synergistic effect, the initial coulombic efficiency and reversible specific capacity of the hard carbon anode material are both improved.

[0017] 2. In this invention, a bimetallic functional differentiation and synergistic strategy is utilized. The oxide nanocrystals converted by the first metal serve as a rigid framework uniformly anchored in the carbon matrix, effectively preventing the structural collapse of the multi-level channels during high-temperature carbonization and long-term cycling, and maintaining the stability of the carbon interlayer spacing. The ultra-micropores and mesopores formed by the in-situ pore formation of the second metal provide a fast transport channel for lithium ions, significantly shortening the diffusion path and reducing concentration polarization. At the same time, the silicon-oxygen-carbon covalent bond network introduced by tetraethyl orthosilicate runs through the carbon framework, enhancing the mechanical strength of the material and effectively suppressing volume expansion and structural fatigue during cycling. This results in the hard carbon anode material possessing both excellent rate performance and cycling stability.

[0018] 3. In this invention, before carbonization, lithium formate molecules are uniformly introduced into the nanopores of the double cross-linked polymer through liquid phase impregnation. These lithium formate molecules decompose in situ during the carbonization process, and the generated lithium ions are captured by the surrounding carbon layer to form a stable lithium-oxygen-carbon bond structure. These pre-embedded lithium ions not only pre-occupy some irreversible sites, but also form a stable, uniform and thin solid electrolyte interface film in advance during the first charging process, which solves the problem of irreversible capacity loss caused by traditional hard carbon materials forming an excessively thick solid electrolyte film due to the consumption of a large number of lithium ions. Attached Figure Description

[0019] Figure 1 The present invention provides a flowchart of a method for preparing a high-performance hard carbon anode material for lithium batteries. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0022] Example 1: A method for preparing a high-performance hard carbon anode material for lithium batteries, comprising the following steps: S1: Preparation of multi-component composite liquid: In the treatment solvent, phloroglucinol, compound one, compound two, tetraethyl orthosilicate and organic acid catalyst are added, and the mixture is stirred at 40°C for 0.5 h to obtain multi-component composite liquid; S2: Crosslinking reaction: Terephthalaldehyde and organic acid catalyst are added to the multi-component composite liquid and reacted at 50°C for 1 h. Then, dimethoxymethane is added and reacted at 100°C for 6 h in a closed system to obtain a double crosslinked polymer. S3: Liquid phase lithium doping: Prepare lithium formate solution, immerse the double cross-linked polymer in lithium formate solution, ultrasonically disperse for 10 min, and then vacuum evaporate the solvent at 40℃ to obtain intermediate; S4: Segmented carbonization: The intermediate is placed in an inert atmosphere and subjected to segmented carbonization to obtain the crude carbonized product. S5: Acid washing and drying: The crude carbonized product is acid washed, water washed and dried to finally obtain high-performance hard carbon anode material for lithium batteries.

[0023] The treatment solvent is a mixture of ethylene glycol dimethyl ether and deionized water in a volume ratio of 9:1, and the total water content of the solvent system is 2wt%.

[0024] The mass ratio of the treatment solvent to phloroglucinol was 5:1.

[0025] The weight ratio of phloroglucinol, compound one, compound two, tetraethyl orthosilicate, lithium formate, terephthalaldehyde, dimethoxymethane, and organic acid catalyst is as follows: phloroglucinol 80 parts, compound one 5 parts, compound two 2 parts, tetraethyl orthosilicate 6 parts, lithium formate 1 part, terephthalaldehyde 30 parts, dimethoxymethane 15 parts, and organic acid catalyst 0.5 parts.

[0026] The first compound is zirconium n-propoxide, the second compound is zinc isopropoxide, and the organic acid catalyst is p-toluenesulfonic acid.

[0027] Based on the amount of resorcinol, the molar ratio of the first compound to resorcinol is 0.03:1, the molar ratio of the second compound to resorcinol is 0.01:1, the molar ratio of lithium formate to resorcinol is 0.02:1, and the molar ratio of tetraethyl orthosilicate to resorcinol is 0.05:1.

[0028] In S1, the amount of organic acid catalyst added is 20% of the total catalyst, and the remaining catalyst is added together with terephthalaldehyde in S2.

[0029] In S3, the lithium formate solution is prepared by dissolving lithium formate in anhydrous ethanol and stirring at 100 r / min for 10 min at 20°C to prepare a lithium formate solution with a concentration of 0.1 mol / L. The liquid-solid mass ratio of the lithium formate solution to the double crosslinked polymer is 3:1.

[0030] The S4 staged carbonization process employs a continuous heating program: the temperature is increased from room temperature to 180℃ at a rate of 0.5℃ / min and held for 1 hour; then the temperature is increased to 300℃ at a rate of 1℃ / min for pre-carbonization for 0.5 hours; next, the temperature is increased to 600℃ at a rate of 2℃ / min and held for 0.5 to 1 hour; finally, the temperature is increased to 850℃ at a rate of 2℃ / min and held for 1 hour. After carbonization, the temperature is allowed to cool naturally to room temperature, and the inert atmosphere is high-purity nitrogen.

[0031] In S5, the pickling process uses 0.3 mol / L hydrochloric acid at 60°C for 2 hours. After pickling, the solution is washed with pure water at 60°C until it is neutral and has a conductivity ≤50 μS / cm. The drying conditions are vacuum drying at 80°C for 6 hours.

[0032] Example 2: A method for preparing a high-performance hard carbon anode material for lithium batteries, comprising the following steps: S1: Preparation of multi-component composite liquid: In the treatment solvent, phloroglucinol, compound 1, compound 2, tetraethyl orthosilicate and organic acid catalyst are added, and the mixture is stirred at 60°C for 1 hour to obtain multi-component composite liquid; S2: Crosslinking reaction: Terephthalaldehyde and organic acid catalyst are added to the multi-component composite liquid and reacted at 60°C for 2 hours. Then, dimethoxymethane is added and reacted at 110°C for 7 hours in a closed system to obtain a double crosslinked polymer. S3: Liquid phase lithium doping: Prepare lithium formate solution, immerse the double crosslinked polymer in lithium formate solution, ultrasonically disperse for 20 min, and then vacuum evaporate the solvent at 50℃ to obtain intermediate; S4: Segmented carbonization: The intermediate is placed in an inert atmosphere and subjected to segmented carbonization to obtain the crude carbonized product. S5: Acid washing and drying: The crude carbonized product is acid washed, water washed and dried to finally obtain high-performance hard carbon anode material for lithium batteries.

[0033] The solvent tetrahydrofuran and deionized water were mixed at a volume ratio of 29:1, and the total water content of the solvent system was 5 wt%.

[0034] The mass ratio of the treatment solvent to phloroglucinol was 12:1.

[0035] The weight ratio of phloroglucinol, compound one, compound two, tetraethyl orthosilicate, lithium formate, terephthalaldehyde, dimethoxymethane, and organic acid catalyst is as follows: phloroglucinol 100 parts, compound one 12 parts, compound two 5 parts, tetraethyl orthosilicate 11 parts, lithium formate 3 parts, terephthalaldehyde 40 parts, dimethoxymethane 22 parts, and organic acid catalyst 2.5 parts.

[0036] The first compound is tetrabutyl titanate, the second compound is magnesium isopropoxide, and the organic acid catalyst is p-toluenesulfonic acid.

[0037] Based on the amount of resorcinol, the molar ratio of the first compound to resorcinol is 0.07:1, the molar ratio of the second compound to resorcinol is 0.03:1, the molar ratio of lithium formate to resorcinol is 0.06:1, and the molar ratio of tetraethyl orthosilicate to resorcinol is 0.12:1.

[0038] In S1, the amount of organic acid catalyst added is 35% of the total amount of catalyst, and the remaining catalyst is added together with terephthalaldehyde in S2.

[0039] In S3, the lithium formate solution is prepared by dissolving lithium formate in anhydrous ethanol and stirring at 200 r / min for 20 min at 30℃ to prepare a lithium formate solution with a concentration of 0.3 mol / L. The liquid-solid mass ratio of the lithium formate solution to the double crosslinked polymer is 6:1.

[0040] The S4 staged carbonization process employs a continuous heating program: the temperature is increased from room temperature to 220℃ at a rate of 0.7℃ / min and held for 2 hours; then the temperature is increased to 350℃ at a rate of 1℃ / min for pre-carbonization for 1 hour; next, the temperature is increased to 650℃ at a rate of 2℃ / min and held for 0.7 hours; finally, the temperature is increased to 950℃ at a rate of 3℃ / min and held for 2 hours. After carbonization, the temperature is naturally cooled to room temperature, and the inert atmosphere is high-purity nitrogen.

[0041] S5 is pickled with 0.7 mol / L hydrochloric acid at 75℃ for 4 hours. After pickling, it is washed with pure water at 70℃ until the washing solution is neutral and the conductivity is ≤50μS / cm. The drying conditions are vacuum drying at 100℃ for 8 hours.

[0042] Example 3: A method for preparing a high-performance hard carbon anode material for lithium batteries, comprising the following steps: S1: Preparation of multi-component composite liquid: In the treatment solvent, phloroglucinol, compound 1, compound 2, tetraethyl orthosilicate and organic acid catalyst are added, and the mixture is stirred at 80°C for 2 hours to obtain multi-component composite liquid; S2: Crosslinking reaction: Terephthalaldehyde and organic acid catalyst are added to the multi-component composite liquid and reacted at 70°C for 3 hours. Then, dimethoxymethane is added and reacted at 120°C for 8 hours in a closed system to obtain a double crosslinked polymer. S3: Liquid phase lithium doping: Prepare lithium formate solution, immerse the double cross-linked polymer in lithium formate solution, ultrasonically disperse for 30 min, and then vacuum evaporate the solvent at 60℃ to obtain intermediate; S4: Segmented carbonization: The intermediate is placed in an inert atmosphere and subjected to segmented carbonization to obtain the crude carbonized product. S5: Acid washing and drying: The crude carbonized product is acid washed, water washed and dried to finally obtain high-performance hard carbon anode material for lithium batteries.

[0043] The treatment solvent is a mixture of ethylene glycol dimethyl ether and deionized water at a volume ratio of 49:1, and the total water content of the solvent system is 10 wt%.

[0044] The mass ratio of the treatment solvent to phloroglucinol was 20:1.

[0045] The weight ratio of phloroglucinol, compound one, compound two, tetraethyl orthosilicate, lithium formate, terephthalaldehyde, dimethoxymethane, and organic acid catalyst is as follows: phloroglucinol 120 parts, compound one 20 parts, compound two 8 parts, tetraethyl orthosilicate 15 parts, lithium formate 5 parts, terephthalaldehyde 50 parts, dimethoxymethane 30 parts, and organic acid catalyst 4 parts.

[0046] The first compound is tetrabutyl titanate, the second compound is magnesium isopropoxide, and the organic acid catalyst is p-toluenesulfonic acid.

[0047] Based on the amount of resorcinol, the molar ratio of the first compound to resorcinol is 0.10:1, the molar ratio of the second compound to resorcinol is 0.05:1, the molar ratio of lithium formate to resorcinol is 0.10:1, and the molar ratio of tetraethyl orthosilicate to resorcinol is 0.20:1.

[0048] In S1, the amount of organic acid catalyst added is 50% of the total amount of catalyst, and the remaining catalyst is added together with terephthalaldehyde in S2.

[0049] In S3, the lithium formate solution is prepared by dissolving lithium formate in anhydrous ethanol and stirring at 300 r / min for 30 min at 40℃ to prepare a lithium formate solution with a concentration of 0.5 mol / L. The liquid-solid mass ratio of the lithium formate solution to the double crosslinked polymer is 8:1.

[0050] The S4 staged carbonization process employs a continuous heating program: the temperature is increased from room temperature to 250℃ at a rate of 1℃ / min and held for 3 hours; then the temperature is increased to 400℃ at a rate of 2℃ / min for pre-carbonization for 1.5 hours; next, the temperature is increased to 700℃ at a rate of 3℃ / min and held for 1 hour; finally, the temperature is increased to 1050℃ at a rate of 5℃ / min and held for 3 hours. After carbonization, the temperature is naturally cooled to room temperature, and the inert atmosphere is high-purity nitrogen.

[0051] S5 is pickled with 1 mol / L hydrochloric acid at 90℃ for 6 hours. After pickling, it is washed with pure water at 80℃ until the washing solution is neutral and the conductivity is ≤50μS / cm. The drying conditions are vacuum drying at 120℃ for 12 hours.

[0052] Comparative Example 1: The difference between this comparative example and Example 1 is that this comparative example does not contain the first compound.

[0053] Comparative Example 2 differs from Example 1 in that it does not contain the second compound.

[0054] Comparative Example 3 differs from Example 1 in that it does not contain tetraethyl orthosilicate.

[0055] Performance testing: The hard carbon anode materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing. Button cell assembly: The hard carbon negative electrode material, conductive carbon black, and binder polyvinylidene fluoride prepared in the embodiments and comparative examples of the present invention were mixed in a mass ratio of 90:5:5. N-methylpyrrolidone was added to form a slurry, which was coated on copper foil and vacuum dried before being punched into circular electrode sheets with a diameter of 12 mm. A lithium metal sheet was used as the counter electrode, Celgard 2400 was used as the separator, and a lithium hexafluorophosphate solution with a volume ratio of 1 mol / L was used as the electrolyte. The solvent was a mixed solvent composed of ethylene carbonate, dimethyl carbonate and diethyl carbonate in a volume ratio of 1:1:1. The CR2032 coin cell was assembled in an argon-filled glove box.

[0056] After assembly, the button cells were allowed to stand for 12 hours to stabilize the open-circuit voltage. Battery performance testing was conducted using a battery performance testing system with a test voltage range of 0.005–3.0V and an ambient temperature controlled at 25℃.

[0057] (1) Determination of initial reversible specific capacity and initial coulombic efficiency: Constant current charge-discharge test was performed at a current density of 0.1C (1C=372mA / g). The initial charge capacity corresponds to the initial lithium-ion intercalation capacity of the hard carbon anode material, and the initial discharge capacity corresponds to the initial reversible specific capacity. The initial coulombic efficiency was calculated by the following formula: ICE = initial reversible specific capacity / initial charge specific capacity × 100%.

[0058] (2) Rate performance test: Charge and discharge 5 times each at current densities of 0.1C, 0.2C, 0.5C, 1C and 2C, and record the reversible specific capacity at each rate. The capacity retention rate at 2C and 0.1C is calculated by the following formula: Rate retention rate = 2C reversible specific capacity / 0.1C reversible specific capacity × 100%.

[0059] (3) Cyclic stability test: 200 constant current charge-discharge cycles at 1C current density, record the reversible specific capacity of the 200th cycle, and calculate the capacity retention rate according to the following formula: Capacity retention rate = 200th reversible specific capacity / 1st reversible specific capacity × 100%.

[0060] Table 1 Performance Test Table of Hard Carbon Anode Materials

[0061] As shown in Table 1, the performance of Examples 1-3 is higher than that of Comparative Examples 1-3; In Examples 1-3, a double crosslinking network was constructed using a stepwise coordination and hierarchical crosslinking strategy, enabling the design and control of the microstructure of hard carbon at the molecular scale. The first metal compound, after carbonization, transforms into zirconium oxide or titanium dioxide nanocrystals. These nanocrystals are uniformly anchored within the carbon framework, effectively suppressing the ordered stacking of carbon layers at high temperatures and expanding the interlayer spacing, providing a wider insertion and extraction channel for lithium ions. Simultaneously, they act as rigid support points to prevent the pore structure from collapsing during cycling, significantly improving the material's cycling stability. The second metal compound generates zinc oxide or magnesium oxide nanoparticles in situ during carbonization. These nanoparticles are uniformly distributed within the carbon matrix and, after elution with dilute acid, form a structure composed of ultrapores and mesopores. The multi-level porous structure provides high-density lithium storage sites through ultra-micropores and mesopores, which serve as rapid lithium-ion transport channels, effectively shortening the diffusion path and thus significantly improving specific capacity and rate performance. Meanwhile, tetraethyl orthosilicate is introduced into the system during the precursor construction stage and forms a silicon-oxygen-carbon covalent bond network through hydrolysis and condensation. The amorphous silicon dioxide remaining after carbonization is anchored in the carbon skeleton by chemical bonds, enhancing the mechanical strength and structural stability of the material. On the other hand, it provides additional lithium storage active sites, further contributing to the reversible capacity. The lithium formate introduced by the liquid phase impregnation method decomposes to generate a lithium-oxygen-carbon bond structure during the carbonization process, achieving uniform doping of lithium at the atomic level, effectively consuming irreversible lithium intercalation sites, and significantly improving the first coulombic efficiency. In Comparative Example 1, without the addition of the first metal compound, the carbon framework is prone to graphitization and rearrangement at high temperatures due to the absence of zirconium or titanium. This reduces the distance between carbon layers, making lithium-ion insertion difficult and resulting in a decrease in capacity. Furthermore, without a framework stabilizer, the pores originally created by the second metal will partially collapse during carbonization, leading to poor lithium-ion flow and changes in rate performance. The collapsed pore walls will generate many defects, which will consume a large number of lithium ions during the first charge to form an excessively thick solid electrolyte film, thus reducing the initial coulombic efficiency. During cycling, the carbon layers without framework support will continue to slowly rearrange, and the pores will become narrower and narrower, demonstrating that the first metal compound is indispensable for maintaining structural stability. Comparative Example 2 did not add a second metal compound, resulting in the absence of zinc or magnesium. During the carbonization process, there were no in-situ generated zinc oxide or magnesium oxide particles to act as pore-forming templates. The carbonized material was dense with very few pores. Lithium ions could only be squeezed between the carbon layers, lacking additional storage space, so the capacity was the lowest. The lack of pores also meant that lithium ions could not diffuse quickly during high current discharge, resulting in the lowest rate performance. The dense material had a larger surface area in contact with the electrolyte, and more lithium ions were consumed when forming a solid electrolyte film, so the initial coulombic efficiency was the lowest. During cycling, the structure without pores was prone to volume expansion and contraction fatigue, resulting in the fastest capacity decay. Comparative Example 3, which does not contain tetraethyl orthosilicate, means that there are no silicon-oxygen-carbon bonds to reinforce the carbon skeleton, and no residual silica to provide additional lithium storage sites. Therefore, the capacity ratio is reduced. The absence of silicon-oxygen-carbon bonds makes the material less mechanically strong during long-term cycling and prone to microcracks. As a result, the retention rate after 200 cycles is also low, leading to a reduction in the upper limit of capacity and cycle life.

[0062] By comparing and analyzing the relevant data in the table, it can be seen that the hard carbon anode material prepared by this invention not only has a good specific capacity, but also excellent initial coulombic efficiency and cycle life. This indicates that the high-performance hard carbon anode material for lithium batteries provided by this invention has a broader market prospect and is more suitable for widespread application.

[0063] In the description of this specification, references to terms such as "an embodiment," "example," and "specific example" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0064] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a high-performance hard carbon anode material for lithium batteries, characterized in that, Includes the following steps: S1: Preparation of multi-component composite liquid: In the treatment solvent, phloroglucinol, compound one, compound two, tetraethyl orthosilicate and organic acid catalyst are added, and the mixture is stirred at 40-80℃ for 0.5-2h to obtain multi-component composite liquid; S2: Crosslinking reaction: Terephthalaldehyde and organic acid catalyst are added to the multi-component composite liquid and reacted at 50-70℃ for 1-3 hours. Then, dimethoxymethane is added and reacted in a closed system at 100-120℃ for 6-8 hours to obtain a double crosslinked polymer. S3: Liquid phase lithium doping: Prepare lithium formate solution, immerse the double cross-linked polymer in lithium formate solution, ultrasonically disperse for 10-30 min, and then vacuum evaporate the solvent at 40-60℃ to obtain intermediate; S4: Segmented carbonization: The intermediate is placed in an inert atmosphere and subjected to segmented carbonization to obtain the crude carbonized product. S5: Acid washing and drying: The crude carbonized product is acid washed, water washed and dried to finally obtain high-performance hard carbon anode material for lithium batteries.

2. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, The treatment solvent is prepared by mixing at least one of ethylene glycol dimethyl ether, tetrahydrofuran, dioxane, and N,N-dimethylformamide with deionized water at a volume ratio of 9 to 49:1, and the total water content of the solvent system is 2 to 10 wt%.

3. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, The mass ratio of the treatment solvent to phloroglucinol is 5–20:

1.

4. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, The weight ratio of the resorcinol, the first compound, the second compound, the tetraethyl orthosilicate, the lithium formate, the terephthalaldehyde, the dimethoxymethane, and the organic acid catalyst is as follows: 80-120 parts of resorcinol, 5-20 parts of the first compound, 2-8 parts of the second compound, 6-15 parts of tetraethyl orthosilicate, 1-5 parts of lithium formate, 30-50 parts of terephthalaldehyde, 15-30 parts of dimethoxymethane, and 0.5-4 parts of the organic acid catalyst.

5. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, The first compound is zirconium n-propoxide or tetrabutyl titanate, the second compound is zinc isopropoxide or magnesium isopropoxide, and the organic acid catalyst is p-toluenesulfonic acid.

6. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, Based on the amount of resorcinol, the molar ratio of the first compound to resorcinol is 0.03 to 0.10:1, the molar ratio of the second compound to resorcinol is 0.01 to 0.05:1, the molar ratio of lithium formate to resorcinol is 0.02 to 0.10:1, and the molar ratio of tetraethyl orthosilicate to resorcinol is 0.05 to 0.20:

1.

7. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, In step S1, the amount of organic acid catalyst added is 20% to 50% of the total catalyst, and the remaining catalyst is added together with terephthalaldehyde in step S2.

8. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, In S3, the lithium formate solution is prepared by dissolving lithium formate in anhydrous ethanol and stirring at 100-300 r / min for 10-30 min at 20-40°C to prepare a lithium formate solution with a concentration of 0.1-0.5 mol / L. The liquid-solid mass ratio of the lithium formate solution to the double crosslinked polymer is 3-8:

1.

9. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, The segmented carbonization in S4 employs a continuous heating program: the temperature is increased from room temperature to 180–250°C at a rate of 0.5–1°C / min and held for 1–3 hours; then, the temperature is increased to 300–400°C at a rate of 1–2°C / min for pre-carbonization for 0.5–1.5 hours; next, the temperature is increased to 600–700°C at a rate of 2–3°C / min and held for 0.5–1 hours; finally, the temperature is increased to 850–1050°C at a rate of 2–5°C / min and held for 1–3 hours. After carbonization, the temperature is naturally cooled to room temperature. The inert atmosphere is high-purity nitrogen.

10. The method for preparing high-performance hard carbon anode material for lithium batteries according to claim 1, characterized in that, In step S5, the pickling is performed using hydrochloric acid with a concentration of 0.3–1 mol / L at 60–90°C for 2–6 hours. After pickling, the solution is washed with pure water at 60–80°C until it is neutral and has a conductivity ≤50 μS / cm. The drying conditions are vacuum drying at 80–120°C for 6–12 hours.